From vibrating molecules to a running shoe: connecting dielectric properties with process feedback in radio-frequency welding of TPU bead foams (2024)
Besides new material solutions, innovative processing technologies are key for working towards a more sustainable future for bead foam products. Compared to standard steam chest molding, innovative radio frequency (RF) welding shows great potential based on its direct energy input, which results in reduced energy consumption. Thus, the present study provides fundamental insights into the correlation of dielectric properties of expanded thermoplastic polyurethane (ETPU) bead foams with the processing behavior. Impedance spectroscopy is used to analyze the complex relative permittivity !∗ of both polymer and respective beads. The dielectric properties of polymers are dictated by their molecular structure and hence resulting dipoles. Thus, significant dependency on temperature and frequency is observed due to changes in chain flexibility and therefore alignment with the oscillating electromagnetic field. As cellular structures, the introduction of a second air phase leads to generally attenuated values at equal trends. Within the RF process, changes, predominantly in the imaginary part of !∗ from initial starting temperatures up to welding, are directly reflected in the power curve as process feedback. Furthermore, temperature evolution and derived heating rate within the bead foams demonstrate excellent conformity with previous results with minor deviations due to the thermal inertia of the fiber optic temperature sensor.